Influence of Lewis Bases on the Mesogenic and Luminescent Properties of Homogeneous Films of Europium(III) Tris(β‐diketonate) Adducts. Issue 3 (19th January 2017) - Knyazev, Andrey A.; Karyakin, Maksim E.; Romanova, Ksenia A.; Heinrich, Benoît; Donnio, Bertrand; Galyametdinov, Yuriy G.
Abstract : A new series of neutral protomesogenic Eu III tris(β‐diketonate) adducts with different Lewis bases have been synthesized. Only one of the complexes is liquid‐crystalline and displays smectic A and nematic mesomorphism over a broad temperature range. Quantum‐chemistry and small‐angle X‐ray scattering methods have permitted the evaluation of the influence of the structure of the Lewis base on the anisometry of Eu III adduct molecules and their subsequent supramolecular organization. The structural features of the presented compounds allow the creation of vitrified optically isotropic and self‐organized films with effective red luminescence. The luminescence spectra of aligned thin films of a liquid‐crystalline Eu III complex are also described. Abstract : Homogeneous films of luminescent europium(III) β‐diketonate complexes with different Lewis bases are prepared. The structure of the Lewis base and the geometric anisotropy of the complex influence the optical characteristics of the films. One of the complexes is liquid‐crystalline and displays smectic A and nematic mesomorphism over a broad temperature range.